When We Were Birds : Poems - Wilkins, Joe (Miller Williams poetry series., 2016)
In When We Were Birds, Joe Wilkins wrestles his attention away from the griefs, deprivations, and high prairies of his Montana childhood and turns toward "the bean-rusted fields and gutted factories of the Midwest," toward ordinary injustice and everyday sadness, toward the imminent birth of his son and his own confusions in taking up the mantle of fatherhood, toward faith and grace, legacy and luck. A panoply of voices are at play--the escaped convict, the late-night convenience store clerk, and the drowned child all have their say--and as this motley chorus rises and crests, we begin to understand something of what binds us and makes us human: while the world invariably breaks all our hearts, Wilkins insists that is the very "place / hope lives, in the breaking." Within a notable range of form, concern, and voice, the poems here never fail to sing. Whether praiseful or interrogating, When We Were Birds is a book of flight, light, and song. "When we were birds," Wilkins begins, "we veered & wheeled, we flapped & looped-- / it's true, we flew."